2016
DOI: 10.1002/mabi.201600328
|View full text |Cite
|
Sign up to set email alerts
|

Osmogen‐Mediated One‐Step Technique of Fabricating Hollow Microparticles for Encapsulation and Delivery of Bioactive Molecules

Abstract: Microparticulate systems composed of biodegradable polymers, such as poly(d,l-lactic-co-glycolic acid) (PLGA), are widely used for controlled release of bioactive molecules. However, the acidic microenvironment within these microparticles, as they degrade, has been reported to perturb the configuration of most encapsulated proteins. In addition, these polymer particles are also reported to suffer from unrealistically slow and incomplete release of proteins. To address these drawbacks, hollow PLGA microparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…By altering the amount of NaCl, microparticles of different cavity sizes and shell thicknesses were obtained, and this is largely driven by the osmotic pressure achieved from the salt. Higher osmolyte concentration allows for more water influx into the emulsion droplet [ 21 ], thus translating to a larger cavity. The cavity diameters achieved were 9.3 ± 3.5 μm, 13.5 ± 4.2 μm and 20.3 ± 8.5 μm, for F2 (3 mg of NaCl), F3 (5 mg of NaCl) and F4 (10 mg of NaCl), respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By altering the amount of NaCl, microparticles of different cavity sizes and shell thicknesses were obtained, and this is largely driven by the osmotic pressure achieved from the salt. Higher osmolyte concentration allows for more water influx into the emulsion droplet [ 21 ], thus translating to a larger cavity. The cavity diameters achieved were 9.3 ± 3.5 μm, 13.5 ± 4.2 μm and 20.3 ± 8.5 μm, for F2 (3 mg of NaCl), F3 (5 mg of NaCl) and F4 (10 mg of NaCl), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…DOX and PTX, from hollow microparticles and compare its efficacy against single-drug-loaded microparticles in tumor spheroids. Hollow particles are preferred over solid particles because the former uses less polymer per particle, and our earlier studies showed that they allow for a complete release of the encapsulated drug [ 21 ]. This maximizes on a higher drug-to-polymer (w/w %) ratio as compared to solid microparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Kharel et al. [ 26 ] reported how hollow‐core microparticles can be obtained through the addition of an osmogen, such as sodium chloride (NaCl). With the addition of NaCl into the polymer solution, the emulsified polymer micelle would entrap a proportion of the salt that results in an osmotic pressure gradient.…”
Section: Figurementioning
confidence: 99%
“…Conventional particles for drug delivery are usually spherical in shape with a variety of morphologies, e.g., solid particles, core/shell particles, and porous particles [21][22][23]. In order to control the release of active agents, solid and core/shell structures provide slow release, while porous structures present a high initial burst release due to high particle porosity [22]. Owing to the release behavior, porous particles are suitable for application as stimuli-responsive gatekeepers for drug delivery systems.…”
Section: Introductionmentioning
confidence: 99%